1998
DOI: 10.1029/98gl01031
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous short wave absorption and atmospheric tides

Abstract: Abstract. Recent studies suggest that either clouds or water vapor in clear air absorb significantly more solar radiation (roughly 25 W m '2 averaged globally) than previously thought.It is interesting, in this connection, that solar diurnal surface pressure tides, which are forced primarily by insolation absorbed in the troposphere, are significantly underestimated in current calculations. In this paper it is shown that increased absorption of the above magnitude results in sizable increases in the migrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The two height regions of phase reversal, one near 9 km and the second one near 13 km, could be satisfactorily simulated, only when the cloud heating was included. This shows the importance of solar short wave heating of clouds, in addition to the other sources, such as PBL and latent heat in generating the non-migrating diurnal tidal oscillations in the lower atmosphere, similar to the findings of Braswell and Lindzen (1998) in the case of diurnal surface pressure oscillation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The two height regions of phase reversal, one near 9 km and the second one near 13 km, could be satisfactorily simulated, only when the cloud heating was included. This shows the importance of solar short wave heating of clouds, in addition to the other sources, such as PBL and latent heat in generating the non-migrating diurnal tidal oscillations in the lower atmosphere, similar to the findings of Braswell and Lindzen (1998) in the case of diurnal surface pressure oscillation.…”
Section: Discussionsupporting
confidence: 69%
“…In view of this fact, the cloud heating assumes significance for the generation of tidal oscillations (Sasi et al, 1998;Braswell and Lindzen, 1998). In a numerical study, Braswell and Lindzen (1998) showed that inclusion of anomalous absorption of solar radiation by clouds could remove the long-standing discrepancy of diurnal migrating surface pressure amplitudes predicted by classical tidal theory. It is possible that this excess cloud heating could generate non-migrating tidal modes, as well.…”
Section: Simulation Of Tidal Fields Using Classical Tidal Theorymentioning
confidence: 99%
“…Comparisons with data revealed significant inadequacies in the representa-tion of S 2 (p) in both reanalyses (Ray, 2001). Similar detailed comparisons for S 1 (p) are missing, but significant discrepancies between theoretical and observed estimates have been noted (Braswell and Lindzen, 1998;Ray, 1998).…”
Section: Introductionmentioning
confidence: 79%
“…The tides have long been studied both in their own right (Chapman and Lindzen, 1970) and for what they potentially reveal about the atmosphere (e.g. Wilkes, 1949;Cooper, 1982;Hamilton, 1983;Braswell and Lindzen, 1998). Our work is partly motivated by modern oceanographic and geodetic apCorrespondence to: R. D. Ray (richard.ray@gsfc.nasa.gov) plications: tidal pressure waves load the ocean and land, and the resulting deformations must be precisely modeled when analyzing, for example, sea level (Ponte and Gaspar, 1999) or gravity (Wahr et al, 1998;Velicogna et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is perhaps not coincidental that observations and theory of the S l surface pressure tide have long been considered discordant: the theory, based on generally accepted absorption models and water-vapor and temperature profiles, underpredicts the observed tidal amplitudes, possibly by more than 30%. As Braswell and Lindzen showed, adoption of 25 W m -2 additional anomalous absorption, either distributed evenly throughout the troposphere or confined simply to a 400-mb cloud level, considerably closes the gap between theory and observation of S • [Braswell and Lindzen, 1998]. This paper is not subject to U.S. copyright.…”
Section: Introductionmentioning
confidence: 99%